Pengaruh Disiplin Kerja, Kompenasi Dan Motivasi Kerja Terhadap Kinerja Karyawan CU Filosofi Petani Pancur Kasih - Sandra Endang Suci Octora; Martha Budiono; Alberd Alberd (Departement of Mathematics Education, 2024)
This study aims to determine the effect of work discipline, compensation, and work motivation on employee performance at CU Filosofi Petani Pancur Kasih. This research uses a quantitative approach with a sample of 30 employees. Data were collected through questionnaires and analysed using multiple regression analysis. The results showed that simultaneously, work discipline, compensation, and work motivation had a significant effect on employee performance with an F value of 3.474 and a significance of 0.030. However, partially, work discipline, compensation, and work motivation have no significant effect on employee performance. The coefficient of determination (R2) of 0.286 indicates that 28.6% of variations in employee performance can be explained by the variables of work discipline, compensation, and work motivation, while the rest is influenced by other factors. This study concludes that work discipline, compensation, and work motivation together have an influence on the performance of employees of CU Filosofi Petani Pancur Kasih, although partially have no significant effect.